EFL LEARNERS’ PERSPECTIVES ON THEIR ENGANGEMENT THROUGH HYBRID LEARNING - Musfirah, Musfirah; Nur, Hasriati (Ekspose: Jurnal Penelitian Hukum dan Pendidikan, 2024)
The present research explores the perspectives of EFL students at IAIN Bone on their engagement in hybrid learning, concentrating on their perceptions and experiences. This research uses qualitative techniques, such as interviews, and observations, to collect information from EFL students engaged in hybrid courses. The results provide light on the attitudes of the learners regarding hybrid learning. The results of this research, the researchers found that there were four learners engagement after doing the observation, they were: personal, academic, intellectual and social engagement. (1) Learners’ personal engagement included things like their needs in learning style, experiences, readiness, hopes, attention, and motivation in learning. (2) Learners’ academic engagement includes organizing, managing time efficiently and their critical thinking. (3) Learners’ intellectual engagement included the frequently of the first quality that lecturer mention when discussing the lessons they have learned from. (4) Learners’ social engagement included learner's capacity to foster relationships and create communities. On the other hand, the result of interviews, it showed that the learners’ perspectives on their engagement toward hybrid learning such as: hybrid learning is flexible and effective, hybrid learning is interactive learning, it can access digital resources and adjust learners’ need, it integrated synchronous and asynchronous learning techniques.